Strategies to improve ellagic acid bioavailability: from natural or semisynthetic derivatives to nanotechnological approaches based on innovative carriers. (3rd July 2020) - Ceci, Claudia; Graziani, Grazia; Faraoni, Isabella; Cacciotti, Ilaria
Abstract: Ellagic acid (EA) is a polyphenolic compound whose dietary consumption is mainly associated with the intake of red fruits, including pomegranates, strawberries, blackberries, blackcurrants, raspberries, grapes or dried fruits, like walnuts and almonds. A number of studies indicate that EA exerts health-beneficial effects against several chronic pathologies associated with oxidative damage, including different kinds of cancer, cardiovascular and neurodegenerative diseases. Furthermore, EA possesses wound-healing properties, antibacterial and antiviral effects, and acts as a systemic antioxidant. However, clinical applications of this polyphenol have been hampered and prevented by its poor water solubility (9.7 ± 3.2 μ g ml −1 in water) and pharmacokinetic profile (limited absorption rate and plasma half-life <1 h after ingestion of pomegranate juice), properties due to the chemical nature of the organic heterotetracyclic compound. Little has been reported on efficient strategies to enhance EA poor oral bioavailability, including chemical structure modifications, encapsulation within nano-microspheres to be used as carriers, and molecular dispersion in polymer matrices. In this review we summarize the experimental approaches investigated so far in order to improve EA pharmacokinetics, supporting the hypothesis that enhancement in EA solubility is a feasible route for increasing its oral absorption.